2017
DOI: 10.3390/app7050475
|View full text |Cite
|
Sign up to set email alerts
|

A Fast and Cost-Effective Detection of Melamine by Surface Enhanced Raman Spectroscopy Using a Novel Hydrogen Bonding-Assisted Supramolecular Matrix and Gold-Coated Magnetic Nanoparticles

Abstract: Abstract:A fast and cost-effective melamine detection approach has been developed based on surface enhanced Raman spectroscopy (SERS) using a novel hydrogen bonding-assisted supramolecular matrix. The detection utilizes was formed due to the strong multiple hydrogen bonding interactions between AOA and melamine. The complex was separated and concentrated to a pellet by an external magnet and used as a supramolecular matrix for the melamine detection. Laser excitation of the complex pellet produced a strong SER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The results showed that the proposed method enables successful determination of ultralow levels of malachite green in real water samples . A SERS active substrate based on Fe 3 O 4 /Au magnetic nanoparticles have been reported for the detection of melamine in milk, achieving a detection limit of 2.5 µg mL –1 . In all cases, the limit of detection of analytes was significantly improved due to the magnetic enrichment and SERS signal enhancement, which were simultaneously achieved by using this class of magneto‐plasmonic materials.…”
Section: Sers‐active Magnetic Nanosorbentsmentioning
confidence: 86%
“…The results showed that the proposed method enables successful determination of ultralow levels of malachite green in real water samples . A SERS active substrate based on Fe 3 O 4 /Au magnetic nanoparticles have been reported for the detection of melamine in milk, achieving a detection limit of 2.5 µg mL –1 . In all cases, the limit of detection of analytes was significantly improved due to the magnetic enrichment and SERS signal enhancement, which were simultaneously achieved by using this class of magneto‐plasmonic materials.…”
Section: Sers‐active Magnetic Nanosorbentsmentioning
confidence: 86%
“…Other than the earlier extensive works on the SERS-based discrimination [65][66][67][68][69], Neng's report also detailed the SERS-based discrimination of melamine by using Fe 3 O 4 /Au magnetic nanoparticles coated with 5-aminoorotic acid (AOA) as a substrate [78]. In their studies, the SERS substrate ( electrode modified with gold nanoparticles and reduced graphene oxide (AuNPs/rGO) was demonstrated by Chen et al towards the discrimination of melamine in food contact materials [75].…”
Section: Melamine Assay By Nanocompositesmentioning
confidence: 99%
“…Surface-enhanced Raman spectroscopy (SERS) is a convenient technique with high sensitivity, fast determination, and low cost, and has been widely applied in food safety analysis [18][19][20][21][22][23][24], environmental monitoring [25,26], protein immunoassay [27][28][29][30][31], and other fields. In recent years, SERS has attracted considerable attention because it can reveal structure, composition, and concentration of target molecules even at a single-molecule level by measuring fingerprint characteristics of target molecules [32,33].…”
Section: Introductionmentioning
confidence: 99%